Interoception: A Multi-Sensory Foundation of Participation in Daily Life - Schmitt, Carolyn M.; Schoen, Sarah (Frontiers in Neuroscience, 2022)
The purpose of this article is to examine evidence that broadens the clinical perspective on interoception as an imperative consideration for individuals with mental health and sensory processing challenges. The central supposition is that interoception is broader than just signals from the viscera. Rather, interoception refers to perceptions of bodily signals and bodily states that construct a subjective representation of the experience. These representations are then utilized for categorizing the sensory attributes and constructing meaning. Thus, this updated conceptualization presents interoception as a complex multidimensional system, with bidirectional features. The interplay between the brain and the body is necessary to maintain homeostasis as well as respond adaptively to the changes in one’s internal and external environment. As a sensory capacity, interoceptive information must be processed and interpreted before it can be integrated into a personal experiential history. Interoception supports both body and mental functions and as such, interoceptive processes support health and wellness by establishing a felt sense of psychological and physiological safety that is foundational to meaningful participation in life. The information presented in this article is central to the pursuit of evidence-based best practices for any professional wishing to integrate consideration of interoception into their clinical practice.